Republic of the Marshall Islands : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of the Marshall Islands. (IMF Staff Country Reports; Country Report ;, 2021)
Strong and timely containment measures have successfully prevented a domestic COVID-19 outbreak but have also weighed on economic activity. The real GDP is estimated to have contracted by 3.3 percent in FY2020 and is projected to further decline by another 1.5 percent in FY 2021 due to continued travel restrictions. Economic activity is expected to pick up in FY2022, as COVID-related restrictions will be relaxed gradually. The government is currently negotiating the renewal of Compact of Free Association (COFA) financial provisions with the United States, but terms remain uncertain. The government is considering to repeal the SOV Act and a bill on establishing a Digital Economic Zone was submitted to the Parliament recently.